2018
DOI: 10.1590/0034-7167-2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

Incidents related to the Hickman® catheter: identification of damages

Abstract: damage or potential risk of damage was present in all incidents analyzed. The need to revise cleaning and obstruction protocols for the maintenance of the permeability of Hickman® catheters was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The importance of the CVC blocking practice with an adequate solution is justified by the risk of infection due to the formation of a fibrin network and to the adherence of bacteria and fungi with loss of permeability (22) . In addition to the risk of infection, the occlusion of the catheter can lead to its early withdrawal, exposing the patient to the risk of a new surgical procedure (6) plus the risk to his safety, since a second catheter is certainly inserted at a more unfavorable moment, within the HSCT process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the CVC blocking practice with an adequate solution is justified by the risk of infection due to the formation of a fibrin network and to the adherence of bacteria and fungi with loss of permeability (22) . In addition to the risk of infection, the occlusion of the catheter can lead to its early withdrawal, exposing the patient to the risk of a new surgical procedure (6) plus the risk to his safety, since a second catheter is certainly inserted at a more unfavorable moment, within the HSCT process.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that investigated incidents related to CVC-SI in patients undergoing HSCT, it was concluded that occlusion was the preponderant event in relation to other possible complications with the Hickman ® catheter (6) . The occlusion of a CVC is a worrying event and it frequently requires the interruption of therapy or, still, the patient's exposure to a new invasive procedure (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Verificado que o achado pode estar relacionado ao rigor no manejo do cateter pela equipe de enfermagem. Os autores ressaltam que a necessidade da infusão de inúmeros medicamentos endovenosos e hemocomponentes exige constante manuseio das vias do cateter, aumentando a probabilidade de contaminação (Pontes et al, 2018).…”
Section: Conhecimento E Aplicação De Bundleunclassified
“…Crateús -Ce, 2022.Avaliar a conformidade da prática assistencial da equipe de enfermagem no manuseio do cateter vascular central na troca de curativos e de equipos em unidade de terapia intensiva.Para uma melhor organização estrutural dos resultados extraídos, optou-se por abordar os estudos de acordo com eixos temáticos. Assim, a descrição dos estudos, bem como os resultados obtidos nos 19 estudos triados foram apresentados em seis tópicos: segurança na inserção do cateter venoso central; conhecimento e aplicação de Bundles; segurança na troca de linhas de infusão e desinfecção de conectores; segurança no preparo e administração de medicamentos; realização e troca de curativos; higienização das mãos.Faz-se necessário enfatizar que a IPCS associada ao CVC pode ocorrer através da infecção intra e extraluminal, onde o cliente apresenta sintomas inespecíficos como febre, mal-estar, calafrios, dor ou exsudado em sítio de inserção do CVC, na ausência de outro foco aparente de infecção, deve-se considerar o quadro na presença do CVC e diante da suspeita, proceder-se à realização da hemocultura a fim de avaliar se há ou não bacteremia associada.De acordo comPontes et al (2018) em seu estudo A6 os danos emocionais estiveram presentes em todos os casos analisados. Pois o paciente, no momento da inserção do CVC é orientado sobre a importância de zelar por ele, juntamente com a equipe de enfermagem.…”
unclassified
“…However, considering that the NDs Impaired skin integrity and Impaired tissue integrity affected all patients, the SICVC was considered to be the main factor associated with these diagnoses. This apparatus is widely used in the HPST processes, and is considered essential due to the venous fragility and the need for simultaneous infusions of incompatible solutions (34)(35)(36) . An article about the use of this device in patients who undergo HPST stated that its management is a responsibility of the nursing service, and that these professionals must be attentive to the discontinuity of the tissue in its place of insertion, planning actions to prevent complications (36) .…”
Section: Nursing Diagnosis After Hematopoietic Stem Cell Transplant Due To Fanconi Anemiamentioning
confidence: 99%